Improved feeding for dairy cattle and poultry in smallholder crop-livestock systems - Mpairwe, Denis; Mutetikka, David (CAB International, 2022)
This chapter describes how cropping systems can be used to supplement feeds to increase dairy and poultry yields. It completes the concept of on-farm integration of crop, livestock and natural resources technologies necessary for sustainable intensification on smallholder farms. The different processes that utilize different feed sources to produce better-quality feed rations for dairy cows and poultry are also discussed.